Isolation, Antimicrobial resistance and genotyping of Escherichia coli from selected wildlife in Sarawak - Kho, Kai Ling. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The potential for dissemination of pathogenic enteric bacteria by wild animal to human is of concern due to their ability to cause endemic and epidemic human diseases. Among the enteric bacteria, Shiga toxin-producing Escherichia coli (E. coli O157:H7) are recognized as an important cause of diarrhea and emerging food borne zoonoses outbreaks. Destruction or disturbances of habitata have been identified as a facto that leads to the emergence of these zoonoses outbreaks. Therefore, this study was performed to compare the occurrence of E. coli and detection of E.coli O157:H7 in selected wildlife comprising of birds, bats and rodents from a natural habitat and disturbed habitats.